2013
DOI: 10.1016/j.socec.2012.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Social conformity and suicide

Abstract: C R E N O S w a s s e t u p i n 1 9 9 3 w i t h t h e p u r p o s e o f o r g a n i s i n g t h e j o i n t r e s e a r c h e f f o r t o f e c o n o m i s t s f r o m t h e t w o S a r d i n i a n u n i v e r s i t i e s ( C a g l i a r i a n d S a s s a r i ) i n v e s t i g a t i n g d u a l i s m a t t h e i n t e r n a t i o n a l a n d r e g i o n a l l e v e l . C R E N o S ' p r i m a r y a i m i s t o i m p r o v e k n o w l e d g e o n t h e e c o n o m i c g a p b e t w e e n a r e a s a n d t o p r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…The measures for openness to experience were adapted from John and Srivastava (1999). Social conformity and online word-of-mouth were assessed based on items from Bussu et al (2013). All items were measured using a five-point Likert scale, ranging from “strongly disagree” (1) to “strongly agree” (5).…”
Section: Data Collection and Samplingmentioning
confidence: 99%
“…The measures for openness to experience were adapted from John and Srivastava (1999). Social conformity and online word-of-mouth were assessed based on items from Bussu et al (2013). All items were measured using a five-point Likert scale, ranging from “strongly disagree” (1) to “strongly agree” (5).…”
Section: Data Collection and Samplingmentioning
confidence: 99%
“…Conversely, isolation and limited social connectivity increase the risk of suicide (Durkheim, 1951/1997; Williams, 2007; Wray et al, 2011). Regions with sparse populations and relatively infrequent interpersonal encounters tend to have higher suicide rates (Bussu, Detotto, & Sterzi, 2013; Lester, 1994). Because we observed that honor states tend to have a lower population density than non-honor states (see Table 1), we controlled for this variable.…”
Section: Alternative Accountsmentioning
confidence: 99%
“…For instance, Park and Lester (2006), reviewing the divorce rate and the SMR in South Korea between 1983 and 2002, found that the SMR was positively associated with the divorce rate for the elderly populations. However, some research has found negative (Baller & Richardson, 2002) or non-significant (Bussu et al, 2013) effects of the divorce rate on the SMR. Meanwhile, suicide research has often considered ethnic heterogeneity (Moore et al, 2014) and residential mobility (Baller & Richardson, 2002) to measure the level of social disintegration.…”
Section: Socioeconomic Covariates Of the Suicide Mortality Ratementioning
confidence: 99%
“…Predicated on Durkheim's notion of anomic suicide, studies have usually investigated the impact of economic crises on the SMR with different economic indices, including the unemployment rate (Breuer, 2015;Yoon et al, 2015), local tax (Joo, 2017) and the house price index (Eun, 2019). Most studies found a positive impact of deteriorating economic conditions on the SMR, but some found non-significant effects (Bussu et al, 2013).…”
Section: Socioeconomic Covariates Of the Suicide Mortality Ratementioning
confidence: 99%
See 1 more Smart Citation